Evaluasi Potensi Energi Listrik Terhadap Pembangkit Listrik Tenaga Minihidro Pada Sungai Terong Di Getasblawong : Penelitian - Farchan Afdhallash Priditya Marthana; Gunawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Getasblawong Village is one of the villages in the highlands that still depends on electricity from outside sources. The village is crossed by a river called Terong River (Kuto River Basin). The river can be used as a Mini Hydro Power Plant (PLTMH) to meet the electricity needs of the village. This study evaluates the performance of power plants to obtain more effective results by assuming the same water drop height. In this study, the power output of the PLTMH will be determined, with supporting data including water discharge and headnet. The focus of this study is to evaluate the electrical energy potential of the PLTMH on the Terong River in Getas Blawong, Pageruyung District, Kendal Regency. The results of the study show that the Terong River has the potential to be utilized for power generation systems, with a water discharge of 2.7 m³/s and a headnet of 189 meters. In this case, the power plant can generate a potential power of 4.4 MW, or 2.2 MW per generator.